Summary survey Climate Smart Villages (CSVs) in Cauca Colombia and El Tuma La Dalia-Nicaragua - Latin America Greenhouse Gas Mitigation Network (International Center for Tropical Agriculture, 2017)
The summary includes data collected from surveys conducted made in the Climate Smart Villages (CSVs) of Cauca-Colombia and El Tuma La Dalia-Nicaragua. The data includes parameters related to soils, cropping systems, land use, land-use changes and livestock in these both villages. The data was them used in Carbon calculator (Cool Farm Tool) to quantify the GHG mitigation potential of previous and current practices.